Scalable VoIP mobility integration and deployment - Epstein, Joseph
Provides practical advice on breaking down the implementation and deployment of voice mobility networks within the office, across the campus, and on the road. Offers a complete primer on enterprise-grade Wi-Fi networking for voice mobility at scale, whether as a single-mode or dual-mode network, including information on the newest 802.11n standard and how these standards directly impact voice mobility. Includes methods of integrating existing or new VoIP networks with 3G+, CDMA 2000, WCDMA, HSPA, and WiMAX cellular networks using fixed/mobile convergence (FMC). This book provides a comprehensive examination of IP-based voice mobility, covering every step in deploying multimodal voice mobility networks. Each segment of the entire voice mobility solution is described with an eye towards the inherent problems of high-scale mobility, from wired infrastructure to end device, across multiple networks and technologies. Voice mobility is introduced and defined at a basic level before the book examines the high-level components of a scalable voice mobility solution. Chapters focus on several types of transport networks in greater depth, including voice quality metrics and testing, high-density enterprise Wi-Fi voice networks, cellular networks, and high-level networking technologies. The security of VoIP networks is also considered. & nbsp;The book explores standalone VoIP networks and finally provides an investigation of the current and upcoming set of fixed/mobile convergence approaches. This book is an invaluable guide for anyone looking towards voice mobility as a solution to real-world business problems: IT managers and executives looking to understand the potential for converting offices to all-wireless; network designers and architects planning on rolling out a fully-mobile voice network; and administrators operating or troubleshooting voice mobility networks. Provides practical advice on breaking down the implementation and deployment of voice mobility networks within the office, across the campus, and on the road. Offers a complete primer on enterprise-grade Wi-Fi networking for voice mobility at scale, whether as a single-mode or dual-mode network, including information on the newest 802.11n standard and how these standards directly impact voice mobility. Includes methods of integrating existing or new VoIP networks with 3G+, CDMA 2000, WCDMA, HSPA, and WiMAX cellular networks using fixed/mobile convergence (FMC).